Implementation of the SERVQUAL Method in Service Quality to Increase Student Satisfaction and Loyalty in Tutoring - Damaianti, Indri; Devi, Wiara Sanchia Grafita Ryana; Afiany, Fitri Dewi; Salam, Fenny Noor; Nurrahmi, Rifni (Global Writing Academica Researching and Publishing, 2022)
The rapid development in the industrial world causes the importance of a company to provide good service to its customers so that customers will feel satisfied and become loyal to the company. This also applies to companies engaged in tutoring services. Improving service quality can be implemented by implementing the SERVQUAL method to increase satisfaction and loyalty for tutoring students. This research will use qualitative methods with data from previous studies. The research concludes how the implementation of the SERVQUAL method in the service delivery process produces satisfaction for customers or students. This customer satisfaction will then continue to be maintained, leading to loyalty, and customers will not go to other competitors.